MEASURING LISTENING SKILLS THROUGH STRATEGY TO NOTE (NOTETAKING) ON KEYWORDS AT SMK N 1 PEMATANGSIANTAR - Gultom, David Gordon; Hutasoit, Patri; Sirait, Salomo Parsaulian (Transpublika Publisher, 2022)
This study aims to determine the role of note taking strategies on listening skills (listening). The research method used in this study is a True research method Experimental Design whose implementation uses the Posttest-Only Control Design type compares the experimental class with the control class. At SMK N 1 PEMATANGSIANTAR, the population of all students in class XI Program Mechanical Engineering Expertise. Samples were taken as many as 52 with a random class technique sampling. The instruments used are MGMP questions and UN questions (Listening). From data processing the results obtained: there are differences in listening learning achievement between before and after using note-taking strategy.